Share price reaction on corporate tax reforms in China - Selamat, Aslam Izah; Syed Mohamed, Mohamed Ariff; Ramadili Mohd, Shamsher Mohamad (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This paper elaborates on the changes in corporate taxation in China to accommodate the government's fiscal expenditure, specifically, the study highlights the effect of major corporate tax reforms in China on firms' share price. The result shows that the price reactions are significantly positive/ negative to corporate tax rate decreases/increases, relatively related to different taxpayer categories. This finding is not in line with the theory of Modigliani and Miller (1958; 1963), which may be due to a larger tax benefit being gained from the tax cut. The correlations between price changes and three firm factors (risk, firm size, debt-equity ratio) among the groups are statistically significant, further validating the result. These findings add to the growing literature seeking to understand China's capital market behaviour and also serves as a test of tax effect involving corporate tax.